Dapatkah Kualitas Produk Menjadi Pertimbangan Dalam Pembelian Smartphone Vivo - Tika Nirmala Sari; Wisnu Rayhan Adhitya; Rina Budiarti (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2023)
The level of consumer involvement in a product purchase can be influenced by the response of a stimulus or stimulus which is generally based on several factors such as product quality. The purpose of writing this study is to describe consumer perceptions of the quality of Vivo products. This research uses quantitative descriptive analysis methods with a sample of 85 people who are students of the management study program of Universitas Potensi Utama. Data collection techniques in this study with questionnaires presented using Likert Scale. The results of this study show that durability is the quality of Vivo products that are considered the weakest. In terms of features, Vivo cameras are also still considered unable to meet the expectations of respondents. In terms of serviceability, Vivo's repair is considered faster and easier than other products. In terms of aesthetics, Vivo's display of both design and color is considered capable of attracting consumers to buy.